Quantifying the Magnitude of Visual Impairment with Multi-Flash Campimetry - Dixon, M; Brussell, E.M (Canadian Journal of Optometry, 2021)
Multi-flash campimetry is a computer implemented clinical psychophysical technique that uses the ability to detect flicker to distinguish between healthy observers and ophthalmological patients. On each trial, a computer randomly selects a point from a 36 point display and begins to flicker it at 5 Hz. The duty cycle of this flickering point (the proportion of the flicker period that is lit), is decreased from 100% in 1 .4% steps each cycle until the observer makes a manual response indicating that flicker has been detected.